LITERATURE REVIEW OF THE INFLUENCE OF EDUCATION ON PREGNANT WOMEN'S KNOWLEDGE ABOUT THE DANGERS OF PREECLAMPSIA - Apra Olivia; Nadia; Yoshie Cristin Agvilera; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Preeclampsia is a condition of high blood pressure that occurs in pregnant women after 20 weeks of gestation, accompanied by the presence of protein in the urine, which can cause the risk of serious complications and even death for the mother and baby. Prevention of preeclampsia is very important because this condition is one of the main causes of maternal mortality in Indonesia. In 2020, there were 4,679 cases of maternal death recorded, with preeclampsia as one of the main causes of death due to hypertension in pregnancy. This study aims to determine how education about the dangers of preeclampsia affects preventive behavior in pregnant women, so that mothers are more aware and take preventive measures. This study used a quasi-experimental method with a one-group pretest-posttest design on pregnant women who were given education using Health Education, booklets, and board game media. Preventive behavior data were measured before and after education with a questionnaire, then analyzed using statistical tests to see significant changes. The discussion includes the definition of preeclampsia, the importance of education, and how education can change the preventive behavior of pregnant women to reduce the risk of complications and maternal death. With good education, it is hoped that knowledge and preventive measures for preeclampsia in pregnant women can increase so that the safety of mothers and babies can be better protected.